Antibiotic prescription analysis of inpatients in a tertiary care teaching hospital - Srinivasa, Jyothsnya; Rajendran, Vijaya (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Antibiotics are one among the commonly prescribed drugs. Patterns of antibiotic resistance widely follows local patterns of antibiotic prescribing and usage. Periodic surveillance of antibiotic prescriptions at regional level are essential to understand and combat antimicrobial resistance. To study the prescribing pattern of antibiotics among inpatients of various specialties in a tertiary care teaching hospital. Method: A prospective observational study of prescribing pattern of antibiotics was conducted among inpatients of various specialties in a tertiary care teaching hospital. Antibiotic prescribing data was collected using a semi structured proforma. The data obtained was analyzed and the conclusions were drawn using descriptive analysis. Results: A total of 1161 prescriptions were collected. 3211 antibiotics were prescribed. Mean average duration of treatment with antibiotics per patient was 11.8 days. Use of 3rd generation cephalosporins, imipenem, piperacillin and vancomycin observed. 75% of antibiotics were prescribed for prophylactic use. Antibiotics prescribed for therapeutic indication were supported by clinical, radiological and other investigations like culture and sensitivity reports. Conclusions: The present study highlights the use of antibiotics for long duration among admitted patients. Implementation of antimicrobial stewardship program with adherence to standard treatment guidelines is essential to combat antimicrobial resistance.